Empowerment of Pinapple Chip Business for Maju Tani Group in Boangmanalu Village Salak Subdistrict Pakpak Bharat Regency - Siahaan, Sabda Dian Nurani; Ulgari, Siti; Pramana, Dodi; Boangmanalu, Eka Putra Dairi (Journal of Community Research and Service, 2023)
Boangmanalu Village is a village located in Pakpak Bharat Regency, North Sumatra Province. The majority livelihoods  of the population are agriculture and the economy is focused on agriculture. Agricultural products from Pakpak Bharat Regency include Gambir, Patchouli, Coffee, Sukat (Taro), Citronella, Pineapple, etc. The partners in this activity are entrepreneurial farmers, named Maju Tani Group in Boangmanalu Village. Since 2021, this group has been producing pineapple chips as an effort to empower pineapple fruit. However, the production of these pineapple chips still has a number of limitations. The problem encountered is the unoptimal implementation of this business in the production side, that the cover of pineapple chips package are not attractive, the manufacturing process pineapple chips that still use conventional methods without the use of machines, and the management wich still unorganized. The solutions offered to this problem are to create a new design of pineapple chip cover packaging, provide a Vacuum Frying machine, and held organizational management training. With this activity, the members of the Maju Tani Group will gain knowledge and experience directly in improving the pineapple chip business and the management of the organization. This service activity also purposed to empower the Maju Tani Group and increase the Pineapple Chips business which ultimately contributes to the improvement of the family economy in Boangmanalu Village.